The Impact of Infographics on Cognitive Enhancement in English Language Students - Andayani, Wuwuh; Murtadho, Fathiaty; Lustyantie, Ninuk (Institut Agama Islam Negeri Palopo, 2025)
This study aimed to explore the impact of infographics on cognitive enhancement in English Language students. Infographics, as a visual medium that combines text and images, are believed to simplify the understanding of complex concepts and improve long-term memory retention. This research adopted a quantitative approach with a field experiment involving two groups of students: an experimental group taught using infographics and a control group taught with conventional methods. Data were collected through cognitive tests before and after the intervention, as well as surveys measuring students’ perceptions of infographics. The results showed that the use of infographics significantly enhances students' understanding of concepts and memory retention in English courses. These findings supported the hypothesis that visual media, such as infographics, can be an effective tool for enhancing cognition in students, particularly in the context of English education. The study also highlighted the importance of integrating visual technologies in learning to stimulate more active and in-depth cognitive interaction.